2017
DOI: 10.4102/ac.v17i1.485
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain management problems in the food processing industry: Implications for business performance

Abstract: Orientation: In emerging economies such as South Africa, the implementation of supply chain management is characterised by significant problems. Despite its continued growth and importance to the economy, the food processing industry in the country remains vulnerable to these problems, which threaten its viability.Motivation for the study: The aim of this study was to investigate supply chain management problems in the food processing industry and their influence on business performance. The study was motivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…This research is based on Primary data collected from a well-structured adopted questionnaire (15) . A total of one hundred ninety questionnaires were dispersed using a Stratified sampling method.…”
Section: Methodsmentioning
confidence: 99%
“…This research is based on Primary data collected from a well-structured adopted questionnaire (15) . A total of one hundred ninety questionnaires were dispersed using a Stratified sampling method.…”
Section: Methodsmentioning
confidence: 99%
“…Acar argued that information sharing can reduce the fluctuation and amplification of information in the supply chain, and that information sharing is more favourable to the upstream of the supply chain than the downstream, suggesting that the upstream of the supply chain should take incentives to promote information sharing [3]. Doning measured the weakening effect of demand and supply information sharing on the "bullwhip effect", and concluded that information sharing is beneficial to the performance optimization of supply chain members [4][5][6], and also researched the problems of information sharing in the supply chain [4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its importance in adopting SCM planning, the supply chain recognizes seven distinct challenges the food processing industry must encounter. Challenges such as the dynamic of human resource management, information and technology adoption, massive facilities requirement, strict supplier relationship management, governmental law and regulation and as well as logistic management system have presented a constant boundary for the hotel industry to adopt [9]. Moreover, challenges related to inventory management have also become apparent as a constraint to be managed.…”
Section: Introductionmentioning
confidence: 99%